2020
DOI: 10.1093/rheumatology/keaa162
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific mortality in native joint septic arthritis: a national population study

Abstract: Objective This national cohort study investigated the incidence, site-specific mortality and prognostic factors of native septic arthritis (SA). Methods Tapping Taiwan’s National Health Insurance Research Database, we identified inpatients with newly diagnosed SA between 1998 and 2012. They were categorized by site of infection and followed to calculate 30-day, 90-day and 1-year mortality. Predictors of mortality were calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 16 publications
1
13
2
Order By: Relevance
“…Delayed or inadequate treatment can result in permanent loss of joint function as well as life-threatening septicaemia. Even with treatment, overall mortality rates related to SA can be significant in adults, ranging from 3% to 23% with 30-day mortality rates of 2%-10% [1][2][3][4][5][6][7][8] and a poor functional outcome in 24% of cases. 9 The incidence of SA is increasing according to some studies.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed or inadequate treatment can result in permanent loss of joint function as well as life-threatening septicaemia. Even with treatment, overall mortality rates related to SA can be significant in adults, ranging from 3% to 23% with 30-day mortality rates of 2%-10% [1][2][3][4][5][6][7][8] and a poor functional outcome in 24% of cases. 9 The incidence of SA is increasing according to some studies.…”
Section: Introductionmentioning
confidence: 99%
“…30 Knees were the most frequently affected joint, and the relative high frequency of hand (wrist/small joints) SA is in line with some recent studies reporting 22%-31% frequencies of SA in the hands. 6,11 In culturepositive SA, Gram stain-positive cocci were found in 62% as in other studies 6,21,22 but with Gram-negative bacteria observed in about a third of cases, these should certainly be considered when initiating empirical antibiotic treatment. 29 While in-hospital mortality in this study was at the lower range (2%-10%) reported, 6,11,31 aspirations (13.7%) and replacement (2.1%) and new onset of inflammatory joint disease were similar across groups and on the lower end of reported SA sequelae.…”
Section: Figures Represent Median Values (Iqr) Frequency (% or Rates [95% Ci])mentioning
confidence: 67%
“…12 Despite variable case definitions (eg, inclusion of prosthetic joint infections), this increasing trend is seen across most studies. 11,12,21,22 behind this rise in SA cases are less clear. A contribution from increasing numbers of diagnostic and therapeutic joint procedures has been described, 9 while other studies suggest a role for aging populations with underlying organ-based comorbidities.…”
Section: Figures Represent Median Values (Iqr) Frequency (% or Rates [95% Ci])mentioning
confidence: 97%
See 1 more Smart Citation
“…Arthritis and other rheumatic conditions can lead to chronic pain, deformity, poor physical functioning, mental health problems, and decreased quality of life over time ( Barbour et al, 2013 , Barbour et al, 2017 , Centers for Disease Control and Prevention, 2017 , Khanna et al, 2011 , Price et al, 2020 ). If not treated, arthritis can also increase the risk of mortality ( England et al, 2018 , Huang et al, 2020 , Kiadaliri et al, 2017 ). Thus, understanding factors associated with arthritis is an important first step towards an effective and efficient allocation of resources in managing arthritis.…”
Section: Introductionmentioning
confidence: 99%